Morphometric evaluation of nasopalatine canal for biological sex determination: a cone beam computed tomography study - Sweethal Devadiga; Ravindranath Vineetha; Keerthilatha M. Pai; Mathangi Kumar; Kalyana Chakravarthy Pentapati (Egyptian Journal of Forensic Sciences)
Abstract Background Forensic odontology plays a crucial role in personal identification in medico-legal cases and massive-scale disasters. The maxillofacial skeleton harbors various landmarks that provide pertinent information in biological sex and age determination. This study aimed to examine the morphology and dimensions of the nasopalatine canal (NPC) in sagittal, coronal, and axial sections on cone beam computed tomography images of individuals of Indian origin. A total of 200 CBCT images (100 males, 100 females) aged 18–65 years were analyzed. The study sought to correlate NPC morphology with age and biological sex. Morphological categories were defined after calibration with a radiologist, and statistical analyses, including chi-square, Fisher’s exact, Mann–Whitney U, and independent t tests, were performed. Inter- and intra-observer reliability was assessed using Cohen’s kappa coefficient. Results The NPC showed considerable morphological variability. Round cross-sectional shape was most prevalent (52%), significantly more in males (61%), while females had a higher frequency of oval shapes (43%). Single canal shape was the most frequent (59.5%) in the longitudinal view on coronal sections. Cylindrical shape was common (51.5%) in the longitudinal view on sagittal sections. External borders varied with age: V-shaped in the 18–30 group (42.5%) and reverse V-shaped in the 31–65 group (45.7%). A single NPC opening was observed in 82.5% of cases, with a significant increase in prevalence in older age groups (91.5%). Males exhibited significantly larger dimensions for the diameter of the nasopalatine foramen and incisive foramen, NPC length, and nasopalatine angle compared to females. No significant age-related variability was noted in NPC dimensions. Conclusion The study highlights the substantial variability in NPC morphology in individuals of Indian origin. The most common findings were a round cross-sectional shape, single canal longitudinally, and a reverse V-shaped external border in older individuals. Biological sex had a significant impact on NPC dimensions, with males exhibiting larger values than females. Hence, the results of morphometric analysis of NPC could be used as a valuable data pool for biological sex determination in forensic research.